Engineering liver organoids-on-a-chip - Zhu, Jiafei; Dressman, Anna; Gall, Kylee; Park, Sunghee Estelle (Frontiers in Lab on a Chip Technologies, 2026)
Advances in stem cell biology and microengineering have led to the emergence of liver organoids-on-a-chip systems, hybrid platforms that integrate self-organizing three-dimensional organoids with microfluidic devices. These technologies enable more physiologically relevant modeling of human liver biology by enhancing organoid maturation, incorporating dynamic cues such as flow and shear stress, and facilitating multicellular interactions across parenchymal and non-parenchymal compartments. As a result, they provide powerful opportunities to investigate liver development, interrogate mechanisms of disease progression, and assess pharmacological responses with higher fidelity than conventional models. Applications span from studying steatohepatitis and fibrosis to evaluating drug-induced liver injury and patient-specific variability in metabolism. In this Review, we highlight recent progress in liver organoids-on-a-chip systems, discuss their potential in personalized medicine and predictive toxicology, and outline current technical challenges and translational opportunities that will shape their future impact on therapeutic discovery and precision health.